On the role of parvocellular (P) and magnocellular (M) pathways in cerebral achromatopsia. - Heywood, C; Cowey, A; Newcombe, F (1994)
We assessed the ability of an achromatopsic patient to detect and discriminate colour and form concealed in a static or dynamic checkerboard display where the luminance differences among adjacent squares were randomly assigned. There were no conditions under which he could discriminate two very different saturated colours from each other. Nevertheless, he could discriminate chromatic from luminance boundaries in static displays when the colour defining the boundary was saturated and the achromatic boundaries all had similar luminance contrast, i.e. varied over a narrow range. However, he could not readily detect chromatic boundaries from among many achromatic boundaries that differed widely in luminance contrast. In addition, he was able to detect chromatic boundaries even when they were concealed by dynamic random luminance masking. His ability to pick out chromatic borders was abolished when desaturated colours were used. However, he was singularly proficient at detecting coloured forms in static or dynamic displays even when the saturation of the colours of which the form was composed were such that they were rendered invisible when concealed as a single square in a checkerboard. This implies that signals about chroma are still available in extracting shape. The patient performed flawlessly when asked to indicate the direction of motion of a horizontal red/green isoluminant grating which was phase shifted by 90 degrees in either direction, demonstrating unequivocally that he has access to the sign of colours that he nevertheless does not perceive.